Implementation of the Job Creation Law in the Establishment of Limited Liability Companies in Indonesia: Challenges and Opportunities - Radea Respati Paramudhita (Jurnal Stagflasi : Ekonomi, Manajemen dan Akuntansi, 2025)
This study examines the implementation of Law Number 11 of 2020 concerning Job Creation in the process of establishing Limited Liability Companies (PT) in Indonesia, focusing on the challenges and opportunities faced by business actors and related institutions. This research uses a qualitative approach with descriptive methods, through legal document analysis, literature review, and in-depth interviews with notaries, entrepreneurs, and business law experts. The results indicate that the implementation of the Job Creation Law in the formation of Limited Liability Companies in Indonesia has had a positive impact in the form of increased efficiency, convenience, and acceleration of the business entity establishment process through the Online Single Submission (OSS) system and the elimination of minimum capital requirements. These reforms open up significant opportunities for Micro, Small, and Medium Enterprises (MSMEs) to independently obtain legal entity status through the Sole Proprietorship scheme. However, this study also identified several challenges, such as the potential for mixing personal and company assets, limited ability to prepare financial reports, and regulatory confusion regarding the implementation of General Meetings of Shareholders (GMS). Thus, although the Job Creation Law has succeeded in creating a more conducive investment climate, its effective implementation still requires regulatory adjustments and ongoing guidance to ensure that the principle of ease of doing business is aligned with legal certainty and protection.